Organophosphorous intoxication and hyperthyroidism - Rao, Bhavana Nagabhushana; Bhavana, Raman (International Journal of Research in Medical Sciences, 2017)
It is well established that transient thyroid dysfunction can occur in many non-thyroid illness. But abnormal thyroid function test in the range of hyperthyroidism is not reported many a times. Here we present two cases of chlorpyrifos intoxication presenting with hyperthyroidism and its implications in the management of the patient in acute illness. Role of atropine in antagonizing muscarinic effects of organophosphorus intoxication is well documented. Interplay between atropine, hyperthyroid state and tachycardia discussed.